The effects of TORC signal interference on lipogenesis in the oleaginous yeast Trichosporon oleaginosus - Bracharz, Felix (BMC Biotechnol, 2017)
BACKGROUND: Oleaginous organisms are a promising, renewable source of single cell oil. Lipid accumulation is mainly induced by limitation of nutrients such as nitrogen, phosphorus or sulfur. The oleaginous yeast Trichosporon oleaginosus accumulates up to 70% w/w lipid under nitrogen stress, while cultivation in non-limiting media only yields 9% w/w lipid. Uncoupling growth from lipid accumulation is key for the industrial process applicability of oleaginous yeasts. This study evaluates the effects of rapamycin on TOR specific signaling pathways associated with lipogenesis in Trichosporon oleaginosus for the first time. RESULTS: Supplementation of rapamycin to nutrient rich cultivation medium led to an increase in lipid yield of up to 38% g/L. This effect plateaued at 40 μM rapamycin. Interestingly, the fatty acid spectrum resembled that observed with cultivation under nitrogen limitation. Significant changes in growth characteristics included a 19% increase in maximum cell density and a 12% higher maximum growth rate. T. oleaginosus only has one Tor gene much like the oleaginous yeast Rhodosporidium toruloides. Consequently, we analyzed the effect of rapamycin on T. oleaginosus specific TORC signaling using bioinformatic methodologies. CONCLUSIONS: We confirm, that target of rapamycin complex 1 (TORC1) is involved in control of lipid production and cell proliferation in T. oleaginosus and present a homology based signaling network. Signaling of lipid induction by TORC1 and response to carbon depletion to this complex appear to be conserved, whereas response to nitrogen limitation and autophagy are not. This work serves as a basis for further investigation regarding the control and induction of lipid accumulation in oil yeasts. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12896-017-0348-3) contains supplementary material, which is available to authorized users.